Are Stocks Too Dangerous for Retirees? A Covered Call Writing Strategy Which Reduces Risk While Harvesting the Expected Market Return - Samsa, Greg (Archives of Business Research, 2020)
A constraint on the typical retiree is that they cannot accept large drops in the value of their retirement portfolio, even temporarily. Traditionally, this has led to the recommendation that they invest in “safe assets”, whose returns are modest albeit consistent. Stocks are considered to be an asset class whose returns are desirable, but is disqualified because of the variability in their returns. Here, we describe an approach which harvests the expected annual return of stocks, with acceptably low variability in returns. This approach could be suitable for retirees, and also for those who anticipate that the market is currently overvalued.